The use of mediation in the settlement of aerospace disputes - sabela sablea (Trigin Publisher, 2023)
Flight delays are an aspect of aerospace where it often happens and the public as passengers experience losses and passengers have the right to compensation and compensation for the incident. The purpose of this study was to determine the arrangements regarding the delay in scheduled departures and assess the responsibility of the airline to passengers regarding the delay in scheduled departures. The research conducted is normative juridical research is a study that deductively begins the analysis of the articles in the legislation governing the problem. Juridical legal research is research that refers to literature studies, while normative is legal research that aims to determine the relationship between one regulation and another and its application in practice. Arrangements regarding flight delays or flight cancellations are regulated in Article 147 of law no. 1 of 2009 and further regulated in Articles 10 and 11 of Minister of Transportation regulation N0. 77, 2011. The airline is obliged to compensate and compensate passengers in the form of transferring to another flight without paying any fees, and provide compensation in the form of material compensation to passengers in the form of money in accordance with the amount of losses suffered by passengers.